2009
DOI: 10.1002/adsc.200900450
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Tandem Reactions of 2‐Halobenzenamines with Isothiocyanates Leading to 2‐Aminobenzothiazoles

Abstract: A highly practical method for the synthesis of 2-aminobenzothiazoles has been developed through an iron-catalyzed tandem reaction. The present tandem process allows the assembly of a wide range of 2-aminobenzothiazoles by the reactions of 2-halobenzenamines with isothiocyanates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 48 publications
1
23
0
2
Order By: Relevance
“…1 H NMR spectra were recorded on a Bruker Avance (400 MHz) spectrometer with TMS as an internal standard in CDCl 3 as solvent. 13 C NMR spectra were recorded on a Bruker Avance (100 MHz) spectrometer in CDCl 3 as solvent. Melting points are uncorrected.…”
Section: General Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR spectra were recorded on a Bruker Avance (400 MHz) spectrometer with TMS as an internal standard in CDCl 3 as solvent. 13 C NMR spectra were recorded on a Bruker Avance (100 MHz) spectrometer in CDCl 3 as solvent. Melting points are uncorrected.…”
Section: General Remarksmentioning
confidence: 99%
“…Recently, the transition-metal-catalyzed tandem reactions of 2-halobenzenamines and isothiocyanates for the synthesis of 2-aminobenzothiazoles have received considerable attention because of their efficiency and low costs. For example, Wu and coworkers described a copper-catalyzed tandem reaction between 2-halobenzenamines and isothiocyanates using the CuI (10 mol %)/1,10-phenanthroline (20 mol%) catalytic system to prepare 2-aminobenzothiazoles [10]; Li and Ding's groups reported ironcatalyzed tandem reactions of 2-halobenzenamines and isothiocyanates leading to 2-aminobenzothiazoles [13,14]. Meanwhile, the ligand-free copper-catalyzed tandem reactions of 2-halobenzenamines and isothiocyanates were also reported [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Bao and co-workers have reported the formation of 2-amino-benzothiazoles 5 by CuI-catalyzed coupling of 2-haloanilines 4 and isothiocyanates (eq 2) [44] Li and co-workers have revealed that thses 2-aminobenzothiazole formation reactions were assisted by an Fe(III) catalyst [45]. These reactions proceed via nucleophilic addition of aniline to isothiocyanate followed by transition-metal-catalyzed intramolecular S-arylation.…”
Section: S N Ar-type C-s C-n or C-o Bond Formation With Heterocumulmentioning
confidence: 99%
“…With these findings [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], the author investigated the transition-metal (Pd, Cu, Fe, etc.) catalyzed coupling of haloarenes 6aa and heterocumulenes.…”
Section: S N Ar-type C-s C-n or C-o Bond Formation With Heterocumulmentioning
confidence: 99%
“…In the synthesis of these compounds, tandem C-S/C-N formation shows obvious advances over other methods due to their facile one-pot procedure [34][35][36][37]. In addition, recent advances in tandem reactions with C-X (X=N, S, O) coupling reactions show their great importance in both methodology development [37][38][39][40][41][42] and natural product synthesis [43]. However, these tandem reactions are always carried out in presence of transition metals.…”
Section: Introductionmentioning
confidence: 99%